U-series ages of young volcanoes from the Southeastern Tibetan Plateau: Holocene eruptions and magma evolution timescales - Zou, Haibo; Guo, Zipei; Peng, Yang; Schmitt, Axel Karl; Fan, Qicheng; Zhao, Yongwei; Ma, Mingjia (Lithos, 2020)
The Tengchong volcanic field in southwestern China represents rare Quaternary volcanic eruptions and associated active geothermal activities on the southeastern margin of the Tibetan plateau. The reported eruption ages for the 3 youngest Tengchong volcanoes (Heikongshan, Dayingshan, Maanshan) are highly variable (3.0-482 ka) because of the challenge to accurately and precisely date young volcanic rocks by radiometric methods. Here we use high-resolution 238U-230Th-226Ra disequilibria to constrain the eruption ages and magma evolution timescales. All 3 young volcanoes exhibit whole-rock (226Ra/230Th) disequilibrium ranging from 1.27 to 1.71, indicating eruption ages of <8 ka (5 half-lives of 226Ra). Eruption ages of 2.9-5.1 ka for Heikongshan, 3.3-4.0 ka for Dayingshan, and 2.9-3.6 ka for Maanshan are constrained by (226Ra/230Th) evolution models. This study thus suggests Holocene eruptions for all 3 volcanoes and represents the first Holocene radiometric age for Dayingshan. We also measured 238U230Th ages of zircons from Heikongshan, Dayingshan, and Maanshan. Zircon age populations are 54.6 ± 13 ka and 94.9 ± 4.1 ka for Heikongshan, 59.6 ± 5.8 and 90.1 ± 8.4 for Dayingshan, and 53.8 ± 8.7 ka and 76.5 ± 11 ka for Maanshan. Magma residence times for all 3 volcanoes are ~50 kyr for a shallow stage and 85 kyr for a deep stage in a two-stage magma chamber system below Tengchong. The similar zircon age distributions for the 3 volcanoes from Tengchong indicate simultaneous magmatism at 90 ka and 55 ka and imply interconnected nature of these volcanoes.
Gesehen am 30.09.2020